Pengaruh Short Video Content TikTok terhadap User Engagement: Peran Mediasi Cognitive Absorption Pada Gen Z Kabupaten Klaten - Ary Sutrischastini; Abdul Hadi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study investigates the impact of TikTok short video content on user engagement among Gen Z in Klaten County, Indonesia, with cognitive absorption serving as a mediating variable. TikTok, a short-video platform renowned for its brief, engaging, and algorithmically personalized content, has witnessed exponential growth, particularly among younger users. The study involved 120 active TikTok users aged 18-26. The analysis utilized SmartPLS software to assess the validity and reliability of the measurement model, followed by an evaluation of the structural model. The results demonstrate that short video content significantly influences user engagement both directly and indirectly through cognitive absorption. Cognitive absorption, marked by focused involvement, temporal dissociation, and heightened enjoyment, acts as a significant mediator. This study concludes that TikTok's content not only entertains but also enhances user engagement by improving the overall user experience. This research contributes to the understanding of digital media interaction by integrating psychological mechanisms into the study of user engagement on short video platforms.